2012
DOI: 10.1517/13543784.2013.748033
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin – a new mitochondria protector for acute severe hemorrhagic shock treatment

Abstract: The study shows that neuronal mitochondrial injury is involved in the genesis of severe shock and PD may be the best choice for protection of neuron against mitochondrial injury in severe shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 39 publications
3
59
0
Order By: Relevance
“…Increased lipid peroxides levels, lysosomal injury and mitochondrial permeability transition pore opening cause swollen mitochondria with poorly defined cristae, decreased mitochondrial membrane potential (DÉ) and reduced ATP content in neurons of rats after 2 h of shock, indicating mitochondrial dysfunction. However, PD evidently inhibits these alterations, which increases the ATP level from 44.14 AE 13.81% to 89.57 AE 9.21% and prolongs survival time from 6.3 AE 5.9 h to 31.6 AE 13.7 h. PD may be the best choice for protection of neuron against mitochondrial injury in severe shock (Wang et al, 2013).…”
Section: Anti-shock Effectsmentioning
confidence: 99%
“…Increased lipid peroxides levels, lysosomal injury and mitochondrial permeability transition pore opening cause swollen mitochondria with poorly defined cristae, decreased mitochondrial membrane potential (DÉ) and reduced ATP content in neurons of rats after 2 h of shock, indicating mitochondrial dysfunction. However, PD evidently inhibits these alterations, which increases the ATP level from 44.14 AE 13.81% to 89.57 AE 9.21% and prolongs survival time from 6.3 AE 5.9 h to 31.6 AE 13.7 h. PD may be the best choice for protection of neuron against mitochondrial injury in severe shock (Wang et al, 2013).…”
Section: Anti-shock Effectsmentioning
confidence: 99%
“…On the basis of our previous experiments [20], PD was dissolved in warm NS (0.3 mL) and administered intravenously.…”
Section: Animals and Mods Modelmentioning
confidence: 99%
“…Improvement in cognitive deterioration after ethanol administration , learning & memory impairment after hypoxicischemic brain injury (Sun et al, 2014), primary hippocampal cells survival rate, down regulation of cyclin dependent kinase 5 activity (Zhang et al) and up regulation of brain derived neurotrophic factor (Sun et al) have been reported after polydatin administration. High dose of polydatin (30 mg/kg/day) has shown an up regulation of glioma associated oncogenhomolog1 (Gli1), patched-1 (Ptch1) & superoxide dismutase 1 (SOD1), down regulation of NF-kB, reduction in infarct volume, brain water contents and improvement in behavioral deficit (Ji et al, 2012).Some authors have suggested that neuro protection offered by polydatin is likely by preventing the mitochondrial injury of the nervous tissue (Wang et al, 2013) or by its antiapoptotic property (Gao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%